Α‐Synuclein stimulation of monoamine oxidase‐B and legumain protease mediates the pathology of Parkinson's disease. (16th May 2018) - Kang, Seong Su; Ahn, Eun Hee; Zhang, Zhentao; Liu, Xia; Manfredsson, Fredric P; Sandoval, Ivette M; Dhakal, Susov; Iuvone, P Michael; Cao, Xuebing; Ye, Keqiang
Abstract: Dopaminergic neurodegeneration in Parkinson's disease (PD) is associated with abnormal dopamine metabolism by MAO‐B (monoamine oxidase‐B) and intracellular α‐Synuclein (α‐Syn) aggregates, called the Lewy body. However, the molecular relationship between α‐Syn and MAO‐B remains unclear. Here, we show that α‐Syn directly binds to MAO‐B and stimulates its enzymatic activity, which triggers AEP (asparagine endopeptidase; legumain) activation and subsequent α‐Syn cleavage at N103, leading to dopaminergic neurodegeneration. Interestingly, the dopamine metabolite, DOPAL, strongly activates AEP, and the N103 fragment of α‐Syn binds and activates MAO‐B. Accordingly, overexpression of AEP in SNCA transgenic mice elicits α‐Syn N103 cleavage and accelerates PD pathogenesis, and inhibition of MAO‐B by Rasagiline diminishes α‐Syn‐mediated PD pathology and motor dysfunction. Moreover, virally mediated expression of α‐Syn N103 induces PD pathogenesis in wild‐type, but not MAO‐B‐null mice. Our findings thus support that AEP‐mediated cleavage of α‐Syn at N103 is required for the association and activation of MAO‐B, mediating PD pathogenesis. Synopsis: Monoamine oxidase‐B (MAO‐B) is important for Parkinson's disease progression, but the exact mechanism is not clear. Here the findings show that α‐Synuclein directly interacts with MAO‐B to regulate its activity causing neurotoxic α‐Synuclein cleavage and dopaminergic cell death. α‐Syn directly binds to MAO‐B and stimulates its enzymatic activity, which triggers asparagine endopeptidase (AEP) activation and subsequent α‐Syn cleavage at N103, leading to dopaminergic neurodegeneration. Overexpression of AEP in SNCA transgenic mice elicits α‐Syn N103 cleavage and accelerates PD pathogenesis, and inhibition of MAO‐B by Rasagiline diminishes α‐Syn mediated PD pathology and motor dysfunction. Virus injection of α‐Syn N103 induces PD pathogenesis in wild‐type, but not MAO‐B knock out mice. Abstract : Direct interaction between two Parkinson's disease‐associated proteins, α‐Synuclein and monoamine oxidase‐B (MAO‐B), regulates MAO‐B activity and neurotoxic cleavage of α‐Synuclein, resulting in dopaminergic neurodegeneration.